Representation without metaphysics - Delgado-Garza, Paloma (Analysis. Journal of Philosophical Research, 2024)
Existing theories of scientific representation often fall short, as they are insufficiently tied to everyday scientific practice. While models are a common and essential tool in daily scientific practice, researchers rarely pause and reflect on what lies behind the tools they regularly use to generate understanding of the phenomena they study. In Inference and Representation: A Study of Models in Science, Mauricio Suárez offers a comprehensive exploration of the inferential conception—a fresh perspective on scientific representation that emphasises the role of models in practice and highlights their representational function.